TINJAUAN YURIDIS TENTANG FAKTOR-FAKTOR PENYEBAB PERBUATAN PIDANA PENGANIAYAAN DENGAN DIRENCANAKAN DAN PIDANA YANG DI JATUHKAN TERHADAP SUBYEK HUKUM PELAKU - Abdul Halim Perkasa (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTcausative factor or the background for a person committed the crime of persecution, there are 2 (two) kinds, namely: Internal factors, are factors that influence the establishment to commit a crime; external factors, there are factors beyond oneself that influence the establishment to commit a crime.Efforts to control criminal acts of persecution carried out in two ways, namely: prevention, preventive efforts; is performed before the crime prevention was occurred by way of preventing crime that did not happen. Prevention efforts are repressive; This reduction in the form of legal action against the perpetrators of the crime, committed or executed after the crime took place.